LANDASAN TEORETIS TEKNOLOGI PENDIDIKAN DALAM PENGEMBANGAN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Tazkia Kautsar Azhar; Siti Nur Andini; Siti Khoerunnisa; Siti Atiqoh (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
This study aims to analyze the theoretical foundations of educational technology in the development of Islamic Religious Education (PAI) learning in the digital era. Employing a qualitative approach with descriptive methods and library research, this study collects data from various literary sources such as textbooks, scientific journals, and relevant articles. The findings indicate that educational technology in the context of PAI serves not only as digital media but also encompasses systematic planning, management, utilization, and evaluation of learning. The theoretical foundations include behaviorism, cognitivism, constructivism, humanism, social learning theory, Technological Pedagogical Content Knowledge and multimedia learning theory. The application of educational technology in PAI has proven to create more interactive, creative, flexible, and student-centered learning, while also enhancing students' motivation and understanding of Islamic values. Nevertheless, the use of technology must remain grounded in pedagogical principles and Islamic ethics, with teacher supervision to prevent negative impacts. Challenges such as limited facilities and teachers' digital competence need to be addressed through continuous training.